Subchronic oral toxicity study of Morinda citrifolia (mengkudu) in Spraque Dawley rats - Shaari, Mohd Rosly; Sithambaram, Shanmugavelu; Marimuthu, Murugaiyah; Hassan, Hadijah; Sapii, Ahmad Tarmizi; Yunus, Nor Idayusni; K., Subramaniam (Universiti Putra Malaysia Press, 2011)
A subchronic oral toxicity study was conducted to evaluate the safety of Morinda citrifolia in Sprague-Dawley (SD) rats. For this purpose, the fruit of Morinda citrifolia were oven dried and ground into powder form before incorporating into diet and fed to SD rats (10 males and 10 females per group) at dose levels of 2000 (low dose) and 5000 (high dose) mg/kg body weight/day for 13 weeks. Clinical observations were recorded, while body weight and feed consumption were measured throughout the study. At the end of the study, all the rats were subjected to a full necropsy. Their blood samples were collected for clinical pathology, whereas selected organs were weighed and tissues were preserved from all the animals. Total protein was found to be significantly lower (p<0.05) in male rats of all the treatment groups. Meanwhile, total white blood cells (3.96 Ã—10Â³/µl) and spleen weight (0.14%) were found to be significantly lower (p<0.05) in female rats of the low dose group. Nevertheless, the differences observed were within the normal range of normal healthy rats that were considered to be not toxicological significance. It was concluded that the no-observed-adverse-effect level (NOAEL) for Morinda citrifolia was 5000 mg/kg body weight/day.